(untitled) (International Journal of Engineering and Computer Science, 2018)
As human race or human society is growing, the wildlife animals or wild animals are in danger. But as per natures rule, every living creature on this earth is important and has important role ecosystem. The domestic animals get misplaced sometimes and finding them is a tedious task. RFID and sensors have been deployed to detect and identify missing animals by affixing them with cheap passive RFID tag and monitoring them with RFID readers. So the proposed system will help us to detect and find the missing animals using RUN protocol. RUN protocol uses slotted aloha for communication between tags and readers. It execute multiple frame for different seeds to reduce the effect of unexpected tags and also it reduces the time of missing tag detection and identification. To obtain optimal frame sizes and minimum no of times aloha frames should be executed to mitigate the effect of unexpected tags. RUN protocol works with multiple readers with overlapping region. It identifies 100% missing tags in the presence of unexpected tags where as other protocol only identifies 60% of missing tags.